Creatures of Habit? What Translators Usually Do with Words - Kenny, Dorothy (Meta, 1998)
AbstractThis paper focuses on some of the methodological and theoretical challenges presented by the investigation of "sanitisation" in translated texts through the analysis of semantic pros- ody. The main hypothesis is that target texts tend to use toned down vocabulary compared with their sources, and that this results in the creation of a "sanitised version of the original."